Pengembangan Media Video Tutorial Pada Mata Pelajaran Bimbingan TIK Kelas VIII SMP - Lydia Meisya; Darmansyah Darmansyah (Jurnal Family Education, 2023)
Based on the problems found in SMP Negeri 6 Sawahlunto in the ICT Guidance subject in class VIII, it was found that the teacher used less attractive learning media so that student learning outcomes were low, there was no video tutorial media used by students as an alternative for learning at home or at school , the learning videos provided by the teacher from YouTube are not in accordance with the learning material, and the time allocation for learning ICT guidance is very short. This study aims to produce valid and practical video tutorial learning media products so that they can be used in ICT guidance lessons for class VIII of SMP Negeri 6 Sawahlunto.This type of research is development research or known as the ADDIE model Research and Development (R&D). Product validity was carried out by 3 people, namely 2 media validators and 1 material validator, while the number of research subjects was 25 class VIII students at SMP Negeri 6 Sawahlunto. The results of the material aspect product validity test obtained an average of 4.66 in the "Very Valid" category. The media validation test from validator I obtained an average of 4.50 in the "Valid" category and validator II obtained an average of 4.93 in the "Very Valid" category. Practicality test obtained an average of 4.59 in the "Very Practical" category. ”. Then the conclusion of the results of this study is that video tutorial media in ICT guidance subjects is very suitable for use in the learning process